MOLECULAR ANALYSIS OF GENETIC STABILITY OF IN-VITRO CONSERVED POTATO MICROPLANTS - Tiwari, Jagesh Kumar; Gupta, Shruti; Gopal, Jai; Kumar, Vinod; Bhardwaj, Vinay; Singh, B P (Potato Journal, 2016)
In vitro conservation and micropropagation are key activities of potato germplasm management for maintenance of true-to-type genotypes. Aim of this study was to analyze genetic stability of three-years in vitro conserved plants (mother plants and their derivatives regenerated after 1st, 2nd and 3rd years of conservation) by random amplified polymorphic DNA (RAPD), inter-simple sequence repeat (ISSR), simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers. A total of 38 (10 RAPDs, 11 ISSRs, 12 SSRs and 5 AFLPs) markers produced total of 360 (42 RAPDs, 54 ISSRs, 96 SSRs and 168 AFLPs) clear, distinct and reproducible bands/peaks. DNA amplification profiles-based cluster analyses showed complete genetic similarity (100%) except for 70-100% by AFLP, among the mother plants and their derivatives in respective cluster of genotype. Cluster analysis based on the Jaccard’s coefficient classified the genotypes into four clusters (I-IV), each cluster consisting of mother plant and its derivatives. Overall, our study shows genetic stability of in vitro conserved microplants for three-years on MS medium supplemented with 20 g/l sucrose, 40 g/l sorbitol and 7 g/l agar at low temperature (7±1°C) under controlled conditions and a safe protocol for regeneration of true-to-type genotypes.